Cross‐sectional and longitudinal associations between gut microbiota composition and cognition in the second year of life: Findings from the Child Health and Resident Microbes study. Issue 7 (13th August 2022) - Matsuyama, Misa; Murtaza, Nida; Morrison, Mark; Davies, Peter S.W.; Hill, Rebecca J.; Loughman, Amy
Abstract: The relationship between the gut microbiota and brain function are receiving increasing research attention. Studies investigating gut microbiota and early childhood neurocognition are limited, particularly in longitudinal measurements. We examined cross‐sectional relationships between gut microbiota of a cohort of otherwise healthy children using 16S rRNA sequencing and their cognitive development measured with Bayley's Scales of Infant Development III at 24 months of age ( n  = 43), and longitudinal relationships between gut microbiota composition at 12 months ( n  = 41) of age and neurodevelopment at 24 months of age. Associations between gut microbiota characteristics and cognitive development were observed both cross‐sectionally and longitudinally, notably with butyrate producing bacteria among some children. Bacterial diversity varied between cross‐sectional and longitudinal observations, where the gut microbiota community of children with lower cognitive scores had a trend toward higher alpha diversity, whereas, in the longitudinal observation, a trend toward reduced alpha diversity was observed. This study is limited by a small sample size and its exploratory nature. Yet, the study contributes to knowledge in the gut microbiota characteristics and early life neurodevelopment, a field of study which is underexplored, presenting opportunities for future larger specific studies.